Probabilistic capacity models and seismic fragility estimates for RC columns subject to corrosion - Choe, Do-Eun; Gardoni, Paolo; Rosowsky, David; Haukaas, Terje (Reliability engineering & system safety, 2008)
In this paper, probabilistic drift and shear force capacity models are developed for corroding reinforced concrete (RC) columns. The developments represent a merger between a probabilistic model for chloride-induced corrosion, a time-dependent corrosion rate, and previously developed probabilistic models for drift and shear force capacity of pristine (undamaged) RC columns. Fragility estimates are obtained for an example corroding column by applying the developed models at given shear and drift demands. Model uncertainties in both the capacity and corrosion models are considered in the fragility estimation, in addition to uncertainties in environmental conditions, material properties, and structural geometry. Sensitivity analyses of the corroding RC column are carried out to identify the parameters to which the reliability of the example column is most sensitive. The developed models consider different combinations of chloride exposure condition, environmental oxygen availability, water-to-cement ratios, and curing conditions. They are applicable to both existing and new RC columns and may be employed for the prediction of service-life and life-cycle cost analysis of RC structures.